Relationship between Umbilical Cord C-peptide and Risk of Hypoglycemia in Infants of Diabetic Mothers - Begum, Mst Nurun Nahar; Hassan, M Quamrul; Azad, Kishwar (Bangladesh Journal of Child Health, 2012)
Objective: To examine the relationship between umbilical cord C-peptide and risk of hypoglycemia in infants of diabetic mothers. Method: Sixty neonates born to diabetic mothers were studied in BIRDEM hospital. Thirty infants who developed hypoglycemia at any time during the first 24 hours of age were considered as cases. Another 30 infants who did not develop hypoglycemia during the first 24 hours were considered as controls. Umbilical cord C-peptide levels were measured in both groups. All babies were screened for hypoglycemia at 4, 6, 8, 12, 18 and 24 hours of life. Blood glucose value of less than 2.6 mmol/l was considered as hypoglycemia. Results: Clinical characteristics of cases and controls and their mothers did not show any significant difference. In 73.3% of cases hypoglycemia was detected by 6 hours of age. Most babies were asymptomatic (93.3%). It was found that IDMs who developed hypoglycemia had significantly higher cord C-peptide level at birth compared to those who remained normoglycemic (4.57±2.50 vs. 2.81± 2.11 ng/ml, P= 0.005). That means, there is significant association between raised level of cord C-peptide and hypoglycemia in IDMs. Conclusion: Hypoglycemia in infants of diabetic mothers associated with raised cord blood C-peptide levels. DOI: http://dx.doi.org/10.3329/bjch.v36i2.13082 Bangladesh J Child Health 2012; Vol 36 (2): 71-75